Adaptation of the cardiovascular system to training loads in elite weightlifters - Jascenko, A.; Draga, V.; Michailov, A. (2001)
Exercises performed in weightlifting training are characterized by a significant amount of weight (up to 20 tons and more) lifted by the athlete during a training session. A tremendous amount of exertion is necessary for the performance of these exercises. During this exertion, intrathoracic pressure increases and venous blood return to the heart may be decreased. Though duration of exertion is no more than 3-5 seconds, it may be repeated 150 times during a training session and may possibly have a negative effect on cardiac output and blood supply to important body systems, particularly the brain. However, during the training process, positive adaptive shifts in the bodies of weightlifters may develop. These shifts guarantee the possibility of lifting more and more weight without any disturbances for the athlete. The indices of a successful adaptation of the cardiovascular system to training loads in weightlifters are shown.